Cell-Type Specific Distribution of T-Type Calcium Currents in Lamina II Neurons of the Rat Spinal Cord - Wu, Jing; Peng, Sicong; Xiao, Linghui; Cheng, Xiaoe; Kuang, Haixia; Zhu, Mengye; Zhang, Daying; Jiang, Changyu; Liu, Tao (Frontiers in Cellular Neuroscience, 2018)
Spinal lamina II (substantia gelatinosa, SG) neurons integrate nociceptive information from the primary afferents and are classified according to electrophysiological (tonic firing, delayed firing, single spike, initial burst, phasic firing, gap firing, and reluctant firing) or morphological (islet, central, vertical, radial, and unclassified) criteria. T-type calcium (Cav3) channels play an essential role in the central mechanism of pathological pain, but the electrophysiological properties and the cell-type specific distribution of T-type channels in SG neurons have not been fully elucidated. To investigate the electrophysiological and morphological features of T-type channel-expressing or -lacking neurons, voltage- and current-clamp recordings were performed on either transverse or parasagittal spinal cord slices. Recording made in transverse spinal cord slices showed that an inward current (IT) was observed in 44.5% of the SG neurons that was fully blocked by Ni2+ and TTA-A2. The amplitude of IT depended on the magnitude and the duration of hyperpolarization pre-pulse. The voltages for eliciting and maximizing IT were −70 mV and −35 mV, respectively. In addition, we found that most of the IT-expressing neurons are tonic firing neurons and exhibit more negative action potential (AP) threshold and smaller difference of AP threshold and resting membrane potential than those neurons lacking IT. Consistently, a specific T-type calcium channel blocker TTA-P2 increased the AP threshold and enlarged the difference between AP threshold and membrane potential (Ihold = 0). Meanwhile, the morphological analysis indicated that most of the IT-expressing neurons are islet neurons. In conclusion, we identify a cell-type specific distribution and the function of T-type channels in SG neurons. These findings might provide new insights into the mechanisms underlying the contribution of T-type channels in sensory transmission.